Implementasi Pengelolaan Zakat Infak dan Sedekah di UPZIS NU Care Lazisnu Desa Mrican Kecamatan Jenangan Kabupaten Ponorogo - Kasanah, Nur (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2021)
Zakat, infaq and alms which are collective social funds that must be managed properly by Zakat Management Organization in order to provide optimal benefits for mustahik. Public will give trust and good image for Zakat Management Organizations which manage their fund transparent, accountable and professionally. This field research with qualitative descriptive approach intends to describe  the management of zakat, infaq and alms at  UPZIS NU Care LAZISNU, Mrican Village, Jenangan District, Ponorogo Regency to be the trusted of ones. The results showed that, it manages zakat fitrah, zakat maal, earth alms, sacrifices, and Koin NU according to comprehensive steps are regulated on Management of Zakat in Law No. 23 of 2011. The steps are fundraising, distribution, empowering and reporting. Fundraising is carried out by promoting the program through social media, pick-up services and account transfer. Distribution and empowering are focused on four programs, namely: education, health, socio-economy and strengthening of the Nahdlatul Ulama (NU) organization. The result of fundraising, distribution and empowering of fund is reported monthly pass through internal Whats App Group (WAG) and its own-self social media accounts such as Facebook, Youtube and InstagramPengelolaan zakat, infak dan sedekah yang transparan, akuntabel dan profesional  oleh LAZ akan menumbuhkan kepercayaan dan citra baik dari donatur dan juga khalayak luas.  Penelitian lapangan yang menggunakan pendekatan kualitatif deskriptif ini bertujuan untuk mengetahui upaya dan langkah-langkah yang dilakukan oleh UPZIS NU Care LAZISNU Desa Mrican Kecamatan Jenangan Kabupaten Ponorogo dalam mengelola dana zakat, infak dan sedekah. Hasil penelitian menunjukkan UPZIS NU Care LAZISNU Desa Mrican Kecamatan Jenangan Kabupaten Ponorogo mengelola zakat fitrah, zakat maal, sedekah bumi, kurban, sedekah rosok dan infak Koin NU melalui tahapan komprehensif sesuai dengan yang tercantum dalam UU No. 23 Tahun 2011 tentang Pengelolaan Zakat, dimulai dari tahapan pengumpulan dana (fundraising), pendayagunaan dan distribusi serta pelaporan. Fundraising dilakukan dengan promosi program melalui sosial media, layanan jemput bola dan transfer rekening. Distribusi dan pendayagunaan di fokuskan pada empat program yaitu: pendidikan, kesehatan, sosial ekonomi dan penguatan organisasi Nahdlatul Ulama (NU). Pelaporan untuk perolehan dana dan kegiatan pentasyarufan dilakukan tiap bulan melalui Whats App Group (WAG) dan publikasi di akun Facebook, Youtube dan Instagram milik UPZIS NU Care LAZISNU Desa Mrican Kecamatan Jenangan Kabupaten Ponorogo.